2009
DOI: 10.1007/s00228-009-0663-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of everolimus versus mycophenolate on blood and lymphocyte cyclosporine exposure in heart-transplant recipients

Abstract: Standard blood CsA levels accurately predict intralymphocytic exposure to CsA in patients concomitantly treated with MMF but not in patients treated with everolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Contradictory findings have been reported for CsA. A study by Gustafsson et al [125] involving heart transplant recipients co-treated with MPA reported a high correlation (r 2 = 0.98, p < 0.001) between CsA concentrations in 2 h postdose (C 2 ) whole blood samples and lymphocyte AUC 0–12h exposure (expressed as ng × h/10– 6 cells). In contrast, a poor correlation was reported in patients co-treated with EVE (r 2 = 0.24, p = 0.18).…”
Section: Intracellular Concentrationmentioning
confidence: 96%
“…Contradictory findings have been reported for CsA. A study by Gustafsson et al [125] involving heart transplant recipients co-treated with MPA reported a high correlation (r 2 = 0.98, p < 0.001) between CsA concentrations in 2 h postdose (C 2 ) whole blood samples and lymphocyte AUC 0–12h exposure (expressed as ng × h/10– 6 cells). In contrast, a poor correlation was reported in patients co-treated with EVE (r 2 = 0.24, p = 0.18).…”
Section: Intracellular Concentrationmentioning
confidence: 96%
“…Concerns that serum cyclosporine levels may not accurately reflect overall tissue cyclosporine exposure when given with concomitant everolimus have been raised [22]. The potential for primary nephrotoxicity from PSIs requires further study.…”
Section: Expert Opinionmentioning
confidence: 98%
“…PSIs that are also substrates for g-glycoprotein increase kidney tissue CsA concentrations when given in combination, possibly potentiating renal toxicity [21]. As opposed to MMF treated patients (where correlation is excellent), CsA tissue exposure has a poor correlation to CsA trough (C0) and 2 h (C2) measurements when co-administered with everolimus [22].…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since CsA exerts its immunosuppressive effect within T-lymphocytes [6], measurement of CsA within these cells may provide more relevant information regarding the immunosuppressive effect of CsA than whole blood concentrations. Several groups have shown data that support this hypothesis in transplant recipients [5,7-10]. We have recently shown that intracellular CsA concentration in T-lymphocytes decreased several days before an acute rejection was possible to diagnose in renal transplants by current standard clinical methods [7].…”
Section: Introductionmentioning
confidence: 95%